Kebahagiaan (Happiness) pada Lansia Muslim Ditinjau dari Partisipasi dalam Aktivitas Keagamaan - Pornamasari, Ria Dessy, Santi Sulandai, S.Psi., M.Ger (2016)
Happiness is highly desirable for every human being, especially for the older people. They want a quieter life, comfortable, and the feeling of safety (feel safe). This study aims to determine is there any relationship between participation in religious activities with happiness in older Muslims. The subject of this research were 100 elder Muslim men and women aged ≥60 years in the Pucangan village, Kartasura district, Sukoharjo. The sampling technique of this research is quota sampling. The research methods in this research used a quantitative method using a measuring instrument happiness scale (Oxford Happiness Questionnaire) and the scale of participation in religious activities. The data analysis technique used the correlation of Pearson Product Moment. Based on the results of data analysis, it was obtained the coefficient correlation (r) 0.424 with sig. (One-tailed) = 0,000 ; p < 0.01, which means there was a very positive significant correlation between participation in religious activities with happiness. The effective contribution of participation in religious activities on the happiness of older muslims was 17.97%, so there's 82.03% of another factors that influence happiness in older muslims other than participation in religious activities. Keywords : religious activity, happiness, elderly